1966
DOI: 10.1128/jb.92.5.1457-1463.1966
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of theViA-hisChromosomal Region inSalmonella

Abstract: The relative chromosomal location of the ViA determinant, a gene required for Vi antigen expression in Salmonella typhosa (and present also in S. typhimurium), was examined in S. typhimurium X S. typhosa matings. The position of this gene was determined with respect to the histidine (his) and methionine (metG) biosynthesis markers, and to the genetic determinants of somatic antigens 5 (0-5) and 4 (0-4) of S. typhimurium. The gene order established by analyses of the hybrid classes resulting from the genetic cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
15
0

Year Published

1968
1968
1992
1992

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 12 publications
4
15
0
Order By: Relevance
“…and H52. The appearance of' the Vi antigen in hybrid H52 is due to its acquisition of the ViA determinant of' S. typhimurium as described previously (3,4). The acquisition of various combinations of S. typhimurium antigens by these S. tvphosa hybrids did not result in any observable change with regard to their mouse virulence level (mean lethal dose > 107 organisms).…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…and H52. The appearance of' the Vi antigen in hybrid H52 is due to its acquisition of the ViA determinant of' S. typhimurium as described previously (3,4). The acquisition of various combinations of S. typhimurium antigens by these S. tvphosa hybrids did not result in any observable change with regard to their mouse virulence level (mean lethal dose > 107 organisms).…”
Section: Resultssupporting
confidence: 60%
“…The donor suspension (0.1 ml) was then spread over 0.1 ml of the recipient lawn on minimal agar selective media. S. typhosa hybrids resulting from the cross between S. typhosa WR4208 and the S. typhimurium Hfr B2 were obtained in previous studies, as described elsewhere (3,4). The procedures employed for serological examination of the hybrids were essentially those described by Edwards and Ewing (2).…”
Section: Methodsmentioning
confidence: 99%
“…As reported previously (4, 5), the majority of his+-selected S. typhimurium hybrids obtained from mating with S. typhosa WR4000 also inherit the closely linked genetic determinant of somatic antigen 9. Because the genetic determinant of this antigen is the allele of the somatic antigen 4 determinant of S. typhimurium (4,5,8), recombination of this locus results in loss of expression of antigen 4 by those S. typhimurium recombinants which express antigen 9. In addition, such recombinants also lose antigen 5 because this antigen cannot be expressed in strains lacking the determinant of antigen 4 (4,5,8).…”
Section: Resultsmentioning
confidence: 99%
“…Vi-expressing Salmonella give rise to nonexpressing variants at frequencies no higher than can be accounted for by spontaneous mutation, and reversion of such nonexpressing variants to the expressig form is rarely seen. The results of previous studies (9,10) have shown that the genes determining Vi antigen expression in Salmonella are situated at two widely separated chromosomal loci, viaA and viaB. The viaA locus is situated near the genes determining histidine biosynthesis, his.…”
mentioning
confidence: 99%